2017
DOI: 10.1002/cctc.201700289
|View full text |Cite
|
Sign up to set email alerts
|

Less Frustration, More Activity—Theoretical Insights into Frustrated Lewis Pairs for Hydrogenation Catalysis

Abstract: The field of frustrated Lewis pair (FLP) chemistry has seen rapid development in only a few years. FLPs have performed most spectacularly in hydrogenation catalysis: a wide variety of FLP‐based systems can catalyze the hydrogenation of a range of different substrates, including imines, enamines, ketones, alkynes, and alkenes. However, FLP‐based hydrogenation catalysts are yet to match the efficiency of their transition‐metal counterparts. The current investigation reveals an important aspect of FLPs that can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 107 publications
1
10
0
Order By: Relevance
“…20b Recently, a computational study was reported proposing that smaller FLPs could yield more active catalysts for the hydrogenation reaction, notably using analogues 2 and 4. 25 Our experimental results support such hypothesis for the C-H bond activation process, but also illustrate the care that needs to be taken when doing computational design. Indeed, the authors proposed 3-centers-2-electrons resting states (Table 3C) for 2 and 4 rather than the experimentally characterized B-H bridged dimers (Table 3D).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…20b Recently, a computational study was reported proposing that smaller FLPs could yield more active catalysts for the hydrogenation reaction, notably using analogues 2 and 4. 25 Our experimental results support such hypothesis for the C-H bond activation process, but also illustrate the care that needs to be taken when doing computational design. Indeed, the authors proposed 3-centers-2-electrons resting states (Table 3C) for 2 and 4 rather than the experimentally characterized B-H bridged dimers (Table 3D).…”
Section: Discussionsupporting
confidence: 70%
“…However, it is important to mention that faster reactivity might ensue when only one of the Lewis pair components is required for a reaction to take place, such as in the interaction of a B–H with a protic reagent . Recently, a computational study was reported proposing that smaller FLPs could yield more active catalysts for the hydrogenation reaction, notably using analogues 2 and 4 . Our experimental results support such a hypothesis for the C–H bond activation process, but also illustrate the care that needs to be taken when doing computational design.…”
Section: Discussionmentioning
confidence: 99%
“…turnover frequency). 22 With this in mind and in the light of the FLP-like reactivity exhibited by heterodinuclear complexes with an explicit M-M bond, 17,23 we decided to investigate the effects derived from finely tuning the balance between metal-metal bond formation 24 and complete metallic frustration in our gold(I)/platinum(0) system. To switch between the two extreme scenarios we have targeted herein three Lewis acidic gold complexes stabilized by terphenyl phosphines, PR2Ar' (R = alkyl; Ar' = C6H3-2,6-Ar2), whose steric parameters were recently investigated by our group (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to phenomena of hydrogen bonding and ion pairing, what makes the complex [ether-H (+) -ether]­[(EWG) 3 B–H (−) ] particularly interesting is that it can be the product of the heterolytic H 2 -cleavage in ether solutions of borane Lewis acids (Scheme ). , Traditionally, transition-metal complexes have played a central role in activation of H 2 and enabling hydrogenation reactions. Relatively recently, it had been demonstrated that the key step of H 2 -activation can be achieved using frustrated Lewis pairs (FLPs) with main group elements. At present, there is a continuing surge of interest in the metal-free activation of H 2 by various types of FLPs and the so-called FLP-catalysis of the hydrogenations of a variety of substrates including those with the unsaturated NC and OC bonds. ,,,, Since Stephan’s seminal work, many reports describe such FLP reactions in the nondonor hydrocarbon or chlorinated/brominated solvents (toluene, dichloromethane, bromobenzene, etc.) and moderately strong donor-solvents (ethers) as well; in the interest of space we are able to mention only a small part of relevant literature.…”
Section: Introductionmentioning
confidence: 99%